Teaching and assessing skills in mathematics - Simpson, Audrey (Dock house : South Africa : Cambridge University press, 2003)
Professional development for teachers is a series of handbooks that offer accessible guidance for teachers around the world.
Include index.
Keywords: Mathematics -- Study and teaching (Secondary).